Low, High and Super Congestion of an Open-Access Resource: Impact under Autarky and Trade, with Aquaculture as Illustration - Maurice Schiff (Global Labor Organization (GLO), 2018)
Analysis of open-access common-property natural resource (NR) has occurred under “low” congestion (LC) – where 𝐴𝐶 and 𝑀𝐶 increase with output 𝑄 – and has for the most part ignored the more important congestion categories where 𝐴𝐶 (𝑀𝐶) is backward-bending (negative) and welfare and NR losses are significantly greater. This paper identifies two such categories, “high” (HC) and “super” (SC) congestion, and examines the impact of open access on steady-state welfare, NR, employment, output and price in a general equilibrium model. Main findings are: i) Welfare and NR costs (and optimal taxes) are a multiple or orders of magnitude greater under HC and (especially) SC than under LC, with trade further – and always – reducing an open-access exporter's NR and welfare. These results are robust to alternative parameter values and functional forms and greatly increase the importance of regulation; ii) An optimal tax raises price and reduces output under autarky in the case of LC and HC but reduces price and raises output under SC, with significantly larger gains; iii) Studies conducted under LC show trade between open-access developing country C1 and regulated but otherwise identical C2 reduces C1's welfare and both C1's and global NR, and though the same holds under HC, the opposite holds under SC; iv) Trade between two open-access countries – say, a developing and an emerging one – with different externality (population) levels raises global output and welfare, improves NR's global efficiency, raises (does not affect) its level, and reduces international inequality; and v) Emigration's welfare gain is much larger under SC than under LC, especially if migration results in LC after migration. Application to other issues and policy implications are provided.
Keywords: D62; F18; Q22; Q27; Q56; 330; Open Access; natural resource; unexamined high congestion; autarky and trade; aquaculture